2017
DOI: 10.1021/acs.jmedchem.6b01007
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel, Highly Potent, and Selective Matrix Metalloproteinase (MMP)-13 Inhibitors with a 1,2,4-Triazol-3-yl Moiety as a Zinc Binding Group Using a Structure-Based Design Approach

Abstract: On the basis of a superposition study of X-ray crystal structures of complexes of quinazoline derivative 1 and triazole derivative 2 with matrix metalloproteinase (MMP)-13 catalytic domain, a novel series of fused pyrimidine compounds which possess a 1,2,4-triazol-3-yl group as a zinc binding group (ZBG) was designed. Among the herein described and evaluated compounds, 31f exhibited excellent potency for MMP-13 (IC = 0.036 nM) and selectivities (greater than 1,500-fold) over other MMPs (MMP-1, -2, -3, -7, -8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…35 With the goal of further expanding the chemical diversity, we next investigated the potential of ZBGs. In addition to accessing unique structure space, we expected that the inclusion of non-carboxylic acid-based ZBGs could impart useful biological properties such as improved pharmacokinetics or permeability into cartilage matrix.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…35 With the goal of further expanding the chemical diversity, we next investigated the potential of ZBGs. In addition to accessing unique structure space, we expected that the inclusion of non-carboxylic acid-based ZBGs could impart useful biological properties such as improved pharmacokinetics or permeability into cartilage matrix.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of the study of the MMP inhibitor without a ZBG aimed at the designing new P1" in our laboratory, we have found that introduction of a small aryl group into the 5-position of the thienopyrimidine-2-carboxamide structure resulted in the excellent potency/selectivity profile (Figure 6). 35 Thus, the 5-arylthienopyrimidine derivative 55 with a benzene ring directly attached to the thiophene ring not only enhanced the inhibitory activity but also improved the selectivity profile compared to the quinazoline 3 ( Table 2, 3 vs 55). Therefore, in a series of derivatives containing ZBGs, small aromatic rings were P1" substituents of choice for the inhibition of MMP-13 (Table 2, 37 and 56).…”
Section: -1 Drug Designmentioning
confidence: 96%
See 3 more Smart Citations